Uzņēmējdarbības vide Latvijā un tās attīstības tendences - Poikāne, Ilva (Latvijas Universitāte, 2014)
Ilvas Poikānes Bakalaura darbs „Latvijas uzņēmējdarbības vide un tās attīstības tendeces” uzrakstīts latviešu valodā, datora salikumā. Apjoms: 60 lpp., darbs satur 19 tabulas, 15 attēlus un ir izmantoti 29 literatūras avoti. Darbā tiek raksturota Latvijas uzņēmējdarbības vide,kā arī tās salīdzinājums ar Baltijas valstīm. Darbā tiek aprakstīti uzņēmējdarbības vides veicinoši faktori un uzņēmējdarbības vides attīstības kavējošie faktori, kā arī aplūkota valsts uzņēmējdarbības vides attistības politika un izteikti priekšlikumi uzņēmējdarbības vides politikas pilnveidošanai. Atslēgvārdi: uzņēmējdarbība ; tautsaimniecība; konkurēt spēja; valsts politika;

Bachelor work „Latvian business environment and its development tendencies” is written in Latvian where is 60 pages, work contains 19 tables and 15 pictures, author used 29 literature sources. The work describes Latvian business environment and its comparison with Baltic States. The work describes the business environment factors contributing to the business environment and the development of inhibitors as well as focuses on the state of the business environment in development policy and suggests policies to improve the business environment. Key words : environment ; national economy ; competitiveness ; goverment policy
Latvian business environment and its development tendencies
Keywords: Ekonomika